Composite lithium sheet, preparation method thereof and lithium ion capacitor
By creating pores on the surface of the cellulose film and filling them with lithium powder to form composite lithium sheets, the problem of long and uneven lithium pre-embedding time in lithium-ion capacitors is solved, and the high energy density and good cycle performance of lithium-ion capacitors are achieved.
Patent Information
- Application Number
- CN202411240596.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-21
AI Technical Summary
The lithium-ion capacitor has a long pre-embedding time and is uneven pre-embedding, resulting in unstable performance.
By making holes on the surface of the cellulose film and filling it with lithium powder to form composite lithium sheets, uniform lithium pre-intercalation is achieved.
The pre-lithium embedding time is shortened, the lithium powder is evenly distributed, and the energy density and cycle performance of the lithium-ion capacitor are improved.
Smart Images

Figure CN119340119A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium pre-embedded in lithium ion capacitors, and in particular to a composite lithium sheet and a preparation method thereof, and a lithium ion capacitor. Background Art
[0002] Lithium-ion capacitors (LICs) are considered as the next generation of energy storage devices due to their high power density and long cycle life. In the relevant technology, the mainstream pre-lithium embedding methods are as follows: Method 1: Uniform pre-lithium embedding is achieved through lithium metal foil, but it is currently difficult to prepare ultra-thin lithium metal foil, which not only brings a burden to lithium-ion capacitors, but also takes a long time and cycle to embed lithium; Method 2: Pre-lithium embedding is achieved by directly adding lithium powder. Although the pre-lithium embedding time can be shortened, there is a problem of uneven dispersion of lithium powder leading to unstable performance of lithium-ion capacitors. Summary of the invention
[0003] In view of this, the present invention provides a composite lithium sheet and a preparation method thereof and a lithium ion capacitor to solve the technical problems of long lithium pre-embedding time and uneven lithium pre-embedding in lithium ion battery containers.
[0004] To achieve the above object, the present invention provides a method for preparing a composite lithium sheet, which is characterized by comprising the following steps:
[0005] S10, forming pores on the surface of the cellulose membrane to obtain a microporous cellulose membrane having micropores on the surface;
[0006] S30, filling lithium powder into the micropores of the microporous cellulose membrane to obtain a composite lithium sheet.
[0007] In some embodiments of the present invention, the thickness of the cellulose film is 40 micrometers to 50 micrometers.
[0008] In some embodiments of the present invention, the pore size of the micropores ranges from 50 micrometers to 100 micrometers.
[0009] In some embodiments of the present invention, the total area of the micropores on the surface of the cellulose membrane accounts for 50% to 80% of the total area of the surface of the cellulose membrane.
[0010] In some embodiments of the present invention, the depth of the micropores accounts for 20% to 60% of the thickness of the cellulose membrane.
[0011] In some embodiments of the present invention, the particle size of the lithium powder ranges from 25 microns to 35 microns.
[0012] In some embodiments of the present invention, the method for preparing the composite lithium sheet further includes the following step S20, mixing polydopamine, water and an aqueous binder to obtain a polydopamine mixed solution, and coating the polydopamine mixed solution onto the surface of the microporous fiber membrane in step S10 to obtain a polydopamine cellulose membrane.
[0013] The present invention also provides a composite lithium sheet prepared by the composite lithium sheet preparation method as described above.
[0014] The present invention also provides a lithium ion capacitor, which comprises the composite lithium sheet as described above.
[0015] In some embodiments of the present invention, the composite lithium sheet is placed between the positive electrode sheet and the negative electrode sheet and separated by a separator.
[0016] The beneficial effects that can be achieved by the present invention are:
[0017] The present invention forms pores on the surface of the cellulose membrane and fills lithium powder in the micropores. The lithium powder can be evenly distributed in the composite lithium sheet by controlling the uniformity of the micropores, thereby achieving uniform pre-embedding of lithium. The lithium powder is filled into the micropores, and it is not easy for the lithium powder to fall over a large area, resulting in high local lithium ion solubility and uneven lithium embedding. In addition, compared with directly pre-embedding lithium with lithium metal foil, it also has the advantage of short lithium pre-embedding time. After a short period of pre-embedding lithium treatment, the lithium ion capacitor can obtain better energy density and cycle performance.
[0018] In addition, the present invention selects cellulose membrane as the main body of the composite lithium sheet. The cellulose membrane has the advantages of light weight and chemical stability. It will not bring weight burden to the lithium ion capacitor and is not easy to react adversely with the electrolyte and other chemical substances in the capacitor, which helps to improve the safety and stability of the capacitor. Moreover, the cellulose membrane also has high mechanical strength and flexibility, which can protect the composite lithium sheet from physical damage and maintain good mechanical strength even after pore formation. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0020] Figure 1 This is a schematic diagram of a cellulose membrane after pores are formed and before lithium powder is filled in an embodiment of the present invention.
[0021] Figure 2 This is a schematic diagram of a cellulose membrane filled with lithium powder after pores are formed according to an embodiment of the present invention.
[0022] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0023] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0026] The present invention provides a composite lithium sheet, comprising the following steps:
[0027] S10, forming pores on the surface of cellulose to obtain a microporous cellulose membrane having micropores on the surface.
[0028] S30, filling lithium powder into the micropores of the microporous cellulose membrane to obtain a composite lithium sheet.
[0029] In the related art, lithium powder can be directly coated on the surface of the cellulose membrane to form a lithium replenishing layer. However, in the process of assembling the capacitor and filling the electrolyte, the lithium powder of the lithium replenishing layer is easy to fall off, or is dissolved by the electrolyte over a large area, resulting in uneven lithium insertion. The present invention, by forming holes on the surface of the cellulose membrane and filling the micropores with lithium powder, is conducive to improving the problem of high local lithium ion solubility and uneven lithium insertion caused by large-scale falling of lithium powder. In addition, the present invention selects cellulose membrane as the main body of the composite lithium sheet. The cellulose membrane has good chemical stability and is not easy to react adversely with the electrolyte and other chemical substances in the capacitor, which helps to improve the safety and stability of the capacitor. Moreover, the cellulose membrane also has high mechanical strength and flexibility, which can protect the composite lithium sheet from physical damage, and even after forming holes, it can still maintain good mechanical strength.
[0030] In some embodiments, the cellulose membrane has a thickness of 40 micrometers to 50 micrometers, and can support single-sided pore formation as well as double-sided pore formation.
[0031] In some embodiments, the pore size of the micropores is 50 microns to 100 microns, which is convenient for filling more lithium powder, increasing the filling amount of lithium powder, improving the lithium insertion effect, and at the same time, it is not easy for lithium powder to fall due to the large pore size.
[0032] In some embodiments, the total area of the micropores on the surface of the cellulose membrane accounts for 50% to 80% of the total surface area of the cellulose membrane, which can not only increase the filling amount of lithium powder and improve the lithium insertion effect, but also prevent the mechanical strength of the cellulose membrane from being reduced due to excessive micropore area, and thus causing damage in a short time under the corrosion of the electrolyte.
[0033] In some embodiments, the depth of the micropores is 20% to 60% of the thickness of the cellulose membrane. For example, the depth may be any value within the range of 20%, 30%, 40%, 50%, 60%, etc.
[0034] In some embodiments, the micropores in the microporous cellulose membrane are equidistantly arranged, which is beneficial for achieving uniform lithium insertion.
[0035] In some embodiments, the micropores in the microporous cellulose membrane have a pore spacing of 100 micrometers to 150 micrometers.
[0036] In some embodiments, laser technology can be used to create pores in the cellulose membrane.
[0037] In the present invention, when forming holes in the cellulose membrane, the mechanical strength of the cellulose membrane will be affected to a certain extent. Under long-term immersion in the electrolyte, the corrosion resistance is weakened and the service life is affected. Therefore, in some embodiments, the method for preparing the composite lithium sheet also includes the following steps: S20, mixing polydopamine, water and an aqueous binder to obtain a polydopamine mixed solution, coating the polydopamine mixed solution on the surface of the microporous cellulose membrane in step S10 to prepare a polydopamine cellulose membrane, and then performing the subsequent step S30 of filling lithium powder to fill the lithium powder into the micropores of the polydopamine cellulose membrane to obtain a composite lithium sheet.
[0038] A layer of polydopamine film is formed on the surface of the polydopamine cellulose film obtained in this embodiment. On the one hand, the polydopamine film provides a protective layer, which can reduce the erosion and damage of the cellulose film by the electrolyte. At the same time, the polydopamine film can also improve the wettability of the cellulose membrane, improve the charging and discharging performance of the lithium ion capacitor and the permeability of the electrolyte, and improve the transmission effect of lithium ions. Moreover, the dynamic covalent bonds in the polydopamine can be reformed when damaged, which can give the composite lithium sheet a certain self-repairing ability and improve the stability of the composite lithium sheet. Polydopamine coating; on the other hand, the polydopamine film contains rich phenolic hydroxyl groups and amino groups. These functional groups can form strong chemical bonds with the cellulose membrane, enhance the mechanical properties and chemical stability of the cellulose membrane, make up for the loss caused by the pore formation of the cellulose membrane, and ensure the service life.
[0039] The present invention prepares the polydopamine film after forming pores in the cellulose membrane, which can reduce the damage of the polydopamine film caused by forming pores. Moreover, the polydopamine film can be covered on the surface of the micropores. The polydopamine film also contains abundant hydrogen bonds, which can enhance the adhesion with the lithium powder, further improve the stability of the lithium powder in the micropores, and prevent the problem of large-scale shedding of lithium powder during the process of assembling the capacitor and filling the electrolyte, resulting in excessive local lithium ion concentration and uneven lithium insertion.
[0040] In some embodiments of step S20, after polydopamine, water and an aqueous binder are mixed to obtain a polydopamine mixed solution, the polydopamine mixed solution is sprayed onto the surface of the microporous cellulose membrane by electrostatic spraying to form a polydopamine film. In this embodiment, polydopamine is sprayed onto the surface of the microporous cellulose membrane by electrostatic spraying. The electrostatic spraying technology can produce fine droplets, thereby forming a uniform and continuous coating on the surface of the microporous cellulose membrane and even in the micropores. While improving the mechanical properties and stability of the microporous cellulose membrane, it can also improve the adhesion of lithium powder, further reducing the risk of lithium powder falling off during capacitor assembly and electrolyte injection, resulting in excessive local lithium ion concentration, and achieving the purpose of uniform lithium insertion.
[0041] In some embodiments, the thickness and coverage position of the polydopamine film can be precisely controlled by adjusting the parameters of the electrostatic spray, such as voltage, spray distance, nozzle aperture, and spray flow rate, so as to cover the micropores without completely filling the micropores.
[0042] In some embodiments, the conditions of electrostatic spraying are as follows: voltage 10 kV to 50 kV, nozzle aperture 0.05 to 0.1 mm, flow rate 5 μL to 10 μL.
[0043] In some embodiments, the aqueous adhesive includes a styrene-butadiene latex adhesive, which can further enhance the bonding force between the polydopamine film and the cellulose film and improve the mechanical strength of the cellulose film.
[0044] In some embodiments, the mass ratio of polydopamine, water and aqueous binder is (10-20): (20-30)-(10-15), so as to form a polydopamine solution with moderate concentration and prepare a light and thin polydopamine film.
[0045] In some embodiments, after water, aqueous adhesive and polydopamine are mixed, they are stirred to achieve uniformity, thereby improving the uniformity of the polydopamine film.
[0046] In some embodiments, lithium powder can be filled into micropores by a scraping method, and then excess lithium powder on the surface of the cellulose membrane is removed to prevent the excess lithium powder on the surface from falling off and causing excessive local lithium ion concentration in the capacitor, followed by rolling to obtain a composite lithium sheet.
[0047] The present invention also provides a capacitor, which includes the composite lithium sheet as described above, wherein the positive electrode sheet, the negative electrode sheet, the composite lithium sheet and the separator are stacked in the order of the composite lithium sheet, the negative electrode sheet, the separator and the positive electrode sheet, and then assembled in a manner well known in the art to obtain the capacitor, and the electrolyte is injected. The capacitor after the electrolyte injection is pre-embedded with lithium. The present invention adds the composite lithium sheet prepared by the present invention to the lithium ion capacitor, and then pre-embeds lithium, which can not only achieve the purpose of uniform lithium embedding, but also effectively shorten the time of pre-embedded lithium. For example, pre-embedded lithium can be completed in 15 days, so that the lithium ion capacitor obtains better energy density and cycle performance.
[0048] In some embodiments, the electrolyte includes a gel electrolyte, which contains a self-repairing polymer network that can quickly fill the damaged area and restore the ion transmission channel when the composite lithium sheet is damaged.
[0049] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0050] Example 1
[0051] Preparation of composite lithium sheets
[0052] S10, using a laser to create holes on one surface of a cellulose membrane with a thickness of 40 microns to obtain a microporous cellulose membrane with micropores on the surface. Figure 1 , Figure 1 This is a schematic diagram of the cellulose membrane after pores are formed but before lithium powder is filled. The micropores in the microporous cellulose membrane are equidistantly arranged, the micropore diameter is 100 microns, the pore spacing is 100 microns, the depth of the micropores accounts for 50% of the thickness of the cellulose membrane, and the total area of the micropores accounts for 70% of the total surface area of the cellulose membrane.
[0053] S20. Mix polydopamine, pure water, and styrene-butadiene latex binder in a mass ratio of 20:20:15 to obtain a polydopamine mixed solution, and spray the polydopamine mixed solution onto the surface of the microporous cellulose membrane by electrostatic spraying to form a polydopamine thin film to obtain a polydopamine cellulose membrane, wherein the conditions of the electrostatic spraying are as follows: voltage 20 Kv, nozzle aperture 0.05 mm, and flow rate 5 μL.
[0054] S30, filling lithium powder with a particle size of 25 microns to 35 microns into the micropores of the polydopamine cellulose membrane by a doctor blade method, then removing excess lithium powder from the surface of the cellulose membrane, and then rolling to obtain a composite lithium sheet, referring to Figure 2 , Figure 2 Schematic diagram of cellulose membrane pores filled with lithium powder.
[0055] Assembling capacitors
[0056] The composite lithium sheet, the negative electrode sheet, the positive electrode sheet, and the separator are stacked in the order of the composite lithium sheet, the negative electrode sheet, the separator, and the positive electrode sheet and packaged in a shell, and the electrolyte lithium hexafluorophosphate is injected. The negative electrode sheet and the composite lithium sheet of the capacitor are electrically connected, and discharged at -30°C to 60°C for 15 days to complete the pre-embedding of lithium in the negative electrode, and then the lithium ion capacitor is obtained through formation and capacity division. The negative electrode sheet, the positive electrode sheet, and the separator of this embodiment can all be selected from the common types in the field.
[0057] Example 2
[0058] Preparation of composite lithium sheets
[0059] Example 2 A composite lithium sheet was prepared by referring to the preparation method of Example 1, except that, in Example 2, the operation of step S20 was not performed, and lithium powder was directly filled into the micropores of the microporous cellulose membrane prepared in step S10.
[0060] Assembling capacitors
[0061] According to Example 1, the composite lithium sheet, the negative electrode sheet, the positive electrode sheet, and the separator are stacked in the order of the composite lithium sheet, the negative electrode sheet, the separator, and the positive electrode sheet and packaged in a shell, and the electrolyte lithium hexafluorophosphate is injected, and the negative electrode sheet and the composite lithium sheet of the capacitor are electrically connected. The discharge is carried out at -30°C to 60°C for 15 days to complete the pre-embedding of lithium in the negative electrode, and then a lithium ion capacitor is obtained through formation and capacity division.
[0062] Example 3
[0063] Example 3 A composite lithium sheet was prepared and pre-embedded with lithium to obtain a lithium ion capacitor in the manner of Example 1, except that the total area of the micropores in Example 3 accounted for 80% of the total area of the surface of the cellulose membrane.
[0064] Comparative Example 1
[0065] In Comparative Example 1, a lithium metal foil of equal size is used to replace the composite lithium sheet of Example 1. The lithium metal foil, the negative electrode sheet, the positive electrode sheet, and the separator are stacked and packaged in a shell in the order of lithium metal foil, negative electrode sheet, separator, and positive electrode sheet. The electrolyte lithium hexafluorophosphate is injected, and the negative electrode sheet and the lithium metal foil of the capacitor are electrically connected. The capacitor is discharged at -30°C to 60°C for 15 days to complete the pre-embedding of lithium in the negative electrode. Then, a lithium ion capacitor is obtained through formation and capacity division.
[0066] Performance Testing
[0067] The energy density of the capacitors prepared in Examples 1 to 3 and Comparative Example 1 and the capacity retention rate after 5000 cycles of cycle testing at a current density of 1 A / g were tested. The test results are shown in Table 1.
[0068] Table 1
[0069] Experimental Group Energy density (Wh / kg) Capacity retention after 5000 cycles (%) Example 1 93 94 Example 2 89 92 Example 3 95 96 Comparative Example 1 85 86
[0070] As can be seen from Table 1, Examples 1 to 3 dig holes on the surface of the cellulose membrane and fill the holes with lithium powder, which can achieve the purpose of uniform lithium insertion, and can also achieve a good lithium insertion effect under the condition of short-term pre-lithium insertion, and have better performance in the energy density and capacity retention rate tests. Comparative Example 1 uses lithium metal foil for pre-lithium insertion. Under the same 15-day pre-lithium insertion time, the energy density and capacity retention rate of the prepared lithium ion capacitor are relatively inferior.
[0071] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a composite lithium sheet, characterized in that: The following steps are involved: S10, forming pores on the surface of the cellulose membrane to obtain a microporous cellulose membrane having micropores on the surface; S30, filling lithium powder into the micropores of the microporous cellulose membrane to obtain a composite lithium sheet.
2. The method for preparing the composite lithium sheet according to claim 1, characterized in that: The thickness of the cellulose film is 40 micrometers to 50 micrometers.
3. The method for preparing the composite lithium sheet according to claim 1, characterized in that: The pore size of the micropores ranges from 50 microns to 100 microns.
4. The method for preparing the composite lithium sheet according to claim 1, characterized in that: The total area of the micropores on the surface of the cellulose membrane accounts for 50% to 80% of the total area of the surface of the cellulose membrane.
5. The method for preparing the composite lithium sheet according to claim 1, characterized in that: The depth of the micropores accounts for 20% to 60% of the thickness of the cellulose membrane.
6. The method for preparing the composite lithium sheet according to claim 1, characterized in that: The particle size of the lithium powder is in the range of 25 microns to 35 microns.
7. The method for preparing the composite lithium sheet according to claim 1, characterized in that: The preparation method of the composite lithium sheet also includes the following steps: S20, mixing polydopamine, water and an aqueous binder to obtain a polydopamine mixed solution, and coating the polydopamine mixed solution onto the surface of the microporous fiber membrane in step S10 to obtain a polydopamine cellulose membrane.
8. The method for preparing the composite lithium sheet according to claim 1, characterized in that: The water-based binder includes styrene-butadiene latex binder.
9. A composite lithium sheet prepared by the method for preparing a composite lithium sheet according to any one of claims 1 to 8.
10. A lithium ion capacitor, characterized in that: The lithium ion capacitor comprises the composite lithium sheet according to claim 9.